How far will you go before switching hands? Handedness on the long pegboard across the lifespan. Issue 5 (25th February 2021) - Scharoun Benson, Sara M.; Williams, Nicole; Tucker, Jessica; Bryden, Pamela J.
Abstract: Handedness is a significant behavioral asymmetry; however, there is debate surrounding the age at which hand preference develops, and little research has been conducted on handedness in older adults. The current study examined performance on the long pegboard, to identify similarities and differences in young children (ages 4–7 years), older children (ages 8–12 years), young adults (ages 18–25 years), and older adults (ages 70+ years). Average time per hole, number of hand switches, and errors were assessed with left‐ and right‐hand starts. A left‐right ratio was computed from the long pegboard, along with laterality quotients from the Waterloo Handedness Questionnaire (WHQ). Results revealed faster performance when participants started the task on the right side of the long pegboard with the right‐hand, coupled with a later switch to the left‐hand. There was a greater number of errors with left‐hand starts, and an earlier switch to the right‐hand. Age was a significant predictor of the average time per hole and number of errors. Long pegboard ratio and WHQ laterality quotient were only correlated for adults. Together, findings offer insight regarding age‐related effects in handedness and support the long pegboard as a useful measure of handedness.